Raw material of ardealite-based geopolymer cementing material, ardealite-based geopolymer cementing material and preparation method and application of ardealite-based geopolymer cementing material

By using a combination of phosphogypsum powder, active blending material and alkali exciter, the problems of poor water resistance, low strength and poor durability of phosphogypsum gelling materials are solved, and the preparation of phosphogypsum base polymer gelling materials with high strength, high water resistance and good durability is achieved.

CN119683886APending Publication Date: 2025-03-25HUBEI UNIV OF ARTS & SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411801103.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing phosphogypsum gelling materials have problems such as poor water resistance, low strength and poor durability, which limits their application in building materials.

Method used

Phosphogypsum powder, active blending materials (such as steel slag powder and red mud powder) and alkali triggers (including water glass, sodium sulfate, silicon slag and calcium lignin sulfonate) are used as raw materials. Through the mixing and stirring process, the hydration reaction between phosphogypsum and active blending materials is promoted to form phosphogypsum base polymer gelling material.

Benefits of technology

The water resistance, strength and durability of phosphogypsum gelling materials are improved, making their performance close to that of silicate cement, and at the same time avoiding the safety hazards of ettringite generated by cement due to hydration reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683886A_ABST
    Figure CN119683886A_ABST
Patent Text Reader

Abstract

The invention discloses a raw material of an ardealite-based geopolymer cementing material, the ardealite-based geopolymer cementing material as well as a preparation method and application of the ardealite-based geopolymer cementing material, and relates to the technical field of building materials. The ardealite-based geopolymer cementing material is prepared from the following raw materials: ardealite powder, an active admixture and an alkali activator, wherein the active admixture comprises at least one of steel slag powder and red mud powder; the alkali activator comprises water glass, sodium sulfate, silicon slag and calcium lignosulphonate. According to the technical scheme, the ardealite powder is used as a raw material, the active admixture is added to improve the later strength and water resistance of the ardealite cementing material, and the compound alkali activator is added to enable the hydration degree of the ardealite and the active admixture to be more complete, so that the performance of the cementing material is further improved. The ardealite cementing material prepared from the raw materials of the ardealite-based geopolymer cementing material provided by the invention can be used for solving the problems of poor water resistance, low strength and poor durability of the existing ardealite cementing material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to raw materials of phosphogypsum-based polymer gelling materials, phosphogypsum-based polymer gelling materials, and a preparation method and application thereof. Background Art

[0002] Phosphogypsum is an industrial byproduct produced during the wet production of phosphoric acid. Every ton of phosphoric acid produced will produce 3.5 to 5.0 tons of phosphogypsum. The main chemical components of phosphogypsum are calcium sulfate dihydrate (CaSO4·2H2O) and Na2SiF6. It also contains a small amount of soluble P2O5, SiO2, Al2O3, fluoride, organic matter and other harmful impurities, as well as a small amount of heavy metals and other impurities. However, the current comprehensive utilization rate of phosphogypsum is only about 30%. The stacking of phosphogypsum not only occupies a large amount of land, but also harmful and toxic elements penetrate into farmland and land with rainwater, causing land, water and air pollution. How to comprehensively utilize phosphogypsum is an urgent problem to be solved in China and even in the world.

[0003] Although there are many ways to utilize phosphogypsum, the utilization rate of phosphogypsum is still very low worldwide. At present, phosphogypsum is mainly used to produce building materials, soil conditioners and chemical raw materials. Using phosphogypsum to prepare building materials is an effective means. Preparing phosphogypsum into phosphogypsum cementitious materials can quickly and massively consume phosphogypsum solid waste. Phosphogypsum itself does not have cementing properties and needs to be calcined to a semi-hydrated or anhydrous state before hydration occurs. It is also an air-hardening material. However, phosphogypsum-based cementitious materials have not yet been widely promoted and utilized. The main problems are as follows: (1) Phosphogypsum cementitious materials are air-hardening cementitious materials. Although they develop strength quickly, are light in weight, flame retardant, and have low energy consumption, compared to silicate cement, phosphogypsum cementitious materials have poor water resistance and low strength. Therefore, its use as a building material is limited; (2) Currently, most methods of utilizing phosphogypsum are to mix phosphogypsum with slag, cement, fly ash, lime, etc. to form a composite cementitious material. Although this composite cementitious material has a high initial strength, the cement in the system will continue to undergo hydration reactions to form calcium sulfonate. As time goes by, the expansion of calcium sulfonate will cause a decrease in strength and even damage to the specimen, posing a safety hazard.

[0004] Therefore, the problems of poor water resistance, low strength and poor durability of phosphogypsum cementitious materials are still urgent problems that need to be solved by those skilled in the art. Summary of the invention

[0005] The main purpose of the present invention is to provide a raw material for a phosphogypsum-based polymer cementitious material, a phosphogypsum-based polymer cementitious material, and a preparation method and application thereof, aiming to solve the problems of poor water resistance, low strength and poor durability of existing phosphogypsum cementitious materials.

[0006] To achieve the above object, the present invention provides a raw material for a phosphogypsum-based polymer cementitious material, wherein the raw material for the phosphogypsum-based polymer cementitious material comprises phosphogypsum powder, an active admixture and an alkali activator;

[0007] Wherein, the active admixture comprises at least one of steel slag powder and red mud powder;

[0008] The alkali activator includes water glass, sodium sulfate, silica slag and calcium lignin sulfonate.

[0009] In one embodiment, the raw material of the phosphogypsum-based polymer cementitious material further includes a retarder, and the retarder includes citric acid.

[0010] In one embodiment, the raw materials of the phosphogypsum-based polymer cementitious material include the following components in parts by mass: 560-650 parts of phosphogypsum powder, 370-435 parts of active admixtures, 3.9-4.5 parts of water glass, 3.9-4.5 parts of sodium sulfate, 5.2-6.1 parts of silicon slag and 0.8-1.2 parts of calcium lignin sulfonate.

[0011] In one embodiment, the raw materials of the phosphogypsum-based polymer cementitious material include the following components in parts by mass: 560 to 650 parts of phosphogypsum powder, 93 to 108 parts of steel slag powder, 280 to 325 parts of red mud powder, 3.9 to 4.5 parts of water glass, 3.9 to 4.5 parts of sodium sulfate, 5.2 to 6.1 parts of silicon slag and 0.8 to 1.2 parts of calcium lignin sulfonate.

[0012] In one embodiment, the particle size of the phosphogypsum powder is less than 200 mesh; and / or,

[0013] The specific surface area of ​​the steel slag powder is 490m 2 / kg~510m 2 / kg; and / or,

[0014] The particle size of the red mud powder is 0.3 mm to 0.5 mm; and / or,

[0015] The silicon slag is silicon slag produced by a process for preparing aluminum fluoride with fluorosilicic acid; and / or,

[0016] The water glass has a modulus of 1.0 to 1.5 and a solid content of 35% to 40%; and / or,

[0017] The molecular weight of the calcium lignin sulfonate is 800-10000, the water content is less than or equal to 8%, and the lignin content is 50-65%.

[0018] The present invention provides a method for preparing a phosphogypsum-based polymer gelling material, wherein the phosphogypsum-based polymer gelling material is prepared by using the raw materials of the phosphogypsum-based polymer gelling material, and the method for preparing the phosphogypsum-based polymer gelling material comprises the following steps:

[0019] The phosphogypsum powder, active admixture and alkali activator are mixed to obtain the phosphogypsum-based polymer gelling material.

[0020] In one embodiment, the step of mixing phosphogypsum powder, active admixture and alkali activator to obtain phosphogypsum-based polymer gelling material comprises:

[0021] Mixing phosphogypsum powder, active admixture and water in a stirrer and stirring at a first rotation speed to obtain a first mixture;

[0022] Mixing the first mixture with a retarder in a stirrer and stirring at a second rotation speed to obtain a second mixture;

[0023] The second mixture is mixed with an alkali activator in a stirrer and stirred at a third speed to obtain a phosphogypsum-based polymer gelling material.

[0024] In one embodiment, the first rotation speed is 500 r / min to 800 r / min; and / or,

[0025] The stirring time at the first speed is 30 min to 50 min; and / or,

[0026] The second speed is 150 r / min to 250 r / min; and / or,

[0027] The stirring time at the second speed is 45 minutes to 60 minutes; and / or,

[0028] The third rotation speed is 150 r / min to 250 r / min; and / or,

[0029] The stirring time at the third rotating speed is 50 min to 60 min.

[0030] The present invention provides a phosphogypsum-based polymer gelling material, wherein the phosphogypsum-based polymer gelling material is prepared according to the preparation method of the phosphogypsum-based polymer gelling material.

[0031] The invention provides an application of the phosphogypsum-based polymer cementitious material in preparing concrete.

[0032] The technical solution of the present invention uses phosphogypsum powder as a raw material, and improves the later strength and water resistance of the phosphogypsum cementitious material by adding an active admixture, and can also improve the workability of the phosphogypsum cementitious material. The addition of a compound alkali activator makes the hydration degree of the phosphogypsum and the active admixture more complete, and further improves the performance of the phosphogypsum cementitious material. Therefore, the use of the raw material of the phosphogypsum-based polymer cementitious material provided by the present invention is conducive to the preparation of a phosphogypsum cementitious material with high strength, good water resistance and good durability, which can solve the problems of poor water resistance, low strength and poor durability of the existing phosphogypsum cementitious material, and is conducive to promoting the high-value utilization of solid wastes such as phosphogypsum, steel slag and silicon slag. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0034] Figure 1 The present invention provides a flow chart of the preparation of a phosphogypsum-based polymer cementitious material according to an embodiment of the present invention.

[0035] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.

[0038] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features limited to "first" and "second" may explicitly or implicitly include at least one of the features. In addition, if "and / or" or "and / or" appears in the full text, its meaning includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or solutions that satisfy both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0039] Phosphogypsum is an industrial byproduct produced during the wet production of phosphoric acid. Every ton of phosphoric acid produced will produce 3.5 to 5.0 tons of phosphogypsum. The main chemical components of phosphogypsum are calcium sulfate dihydrate (CaSO4·2H2O) and Na2SiF6. It also contains a small amount of soluble P2O5, SiO2, Al2O3, fluoride, organic matter and other harmful impurities, as well as a small amount of heavy metals and other impurities. However, the current comprehensive utilization rate of phosphogypsum is only about 30%. The stacking of phosphogypsum not only occupies a large amount of land, but also harmful and toxic elements penetrate into farmland and land with rainwater, causing land, water and air pollution. How to comprehensively utilize phosphogypsum is an urgent problem to be solved in China and even in the world.

[0040] Although there are many ways to utilize phosphogypsum, the utilization rate of phosphogypsum is still very low worldwide. At present, phosphogypsum is mainly used to produce building materials, soil conditioners and chemical raw materials. Using phosphogypsum to prepare building materials is an effective means. Preparing phosphogypsum into phosphogypsum cementitious materials can quickly consume a large amount of phosphogypsum solid waste. Phosphogypsum itself does not have cementing properties. It needs to be calcined to a semi-hydrated or anhydrous state before a hydration reaction can occur, and it is an air-hardening material. However, phosphogypsum-based cementitious materials have not been widely promoted and utilized. The main problems are as follows: (1) Phosphogypsum cementitious materials are air-hardening cementitious materials. Although they develop strength quickly, are light in weight, flame retardant, and have low energy consumption, compared with silicate cement, phosphogypsum cementitious materials have poor water resistance and low strength. Therefore, its use as a building material is limited; (2) At present, most methods of using phosphogypsum are to mix phosphogypsum with slag, cement, fly ash, lime, etc. to make a composite cementitious material. Although this composite cementitious material has a high initial strength, the cement in the system will continue to undergo hydration reaction to form calcium sulfonate. As time goes by, the calcium sulfonate expands, causing the strength to decrease or even the specimen to be damaged, posing a safety hazard. Therefore, the problems of poor water resistance, low strength and poor durability of phosphogypsum cementitious materials are still problems that technicians in this field urgently need to solve.

[0041] In view of this, the present invention provides a raw material for a phosphogypsum-based polymer cementitious material, wherein the raw material for the phosphogypsum-based polymer cementitious material comprises phosphogypsum powder, an active admixture and an alkali activator;

[0042] Wherein, the active admixture comprises at least one of steel slag powder and red mud powder;

[0043] The alkali activator includes water glass, sodium sulfate, silica slag and calcium lignin sulfonate.

[0044] The raw materials of the phosphogypsum-based polymer gelling material of the present invention are selected from solid wastes such as phosphogypsum, steel slag, and red mud as the main raw materials, wherein the raw material is phosphogypsum, and steel slag and red mud are active admixtures. The CaO and SiO2 components in the steel slag undergo hydration reaction to generate CSH gel (hydrated calcium silicate gel), which can improve the strength and water resistance of the hardened body and improve the workability; under the alkali excitation, the original stable silicon oxygen and aluminum oxygen bonds of the red mud are broken, and sodium aluminosilicate and dicalcium silicate are generated, which can significantly improve the later strength and water resistance of the hardened body. Conventional alkali activators usually use sodium hydroxide, potassium hydroxide, sodium silicate, sodium carbonate, potassium carbonate and sodium sulfate, etc. The technical solution of the present invention uses water glass, sodium sulfate, silicon slag and calcium lignin sulfonate at the same time. Compared with conventional alkali activators, the generation of hydration products is strengthened through the dual effects of inorganic synergists and organic synergists. Among them, adding water glass to the raw materials can react chemically with Ca(OH)2 in the cementitious material to generate CaSiO3 and NaOH, which promotes the hydration and hardening of the cementitious material and improves the compressive strength. Water glass also has excellent bonding properties, can block the pores in the cementitious material, increase the density of the cementitious material system, and improve the compressive strength and structural strength of the composite cementitious material. Adding sodium sulfate, silica slag and calcium lignin sulfonate can improve the alkali excitation effect. The addition of water glass and sodium sulfate accelerates the hydration of tricalcium aluminate; the addition of silica slag promotes the formation of hydrated calcium silicate; the addition of calcium lignin sulfonate promotes the dispersibility of cementitious material particles in the slurry. Therefore, the technical solution of the present invention can make the various components in the cementitious material coordinate and promote the complete degree of hydration through the combination of inorganic salts and surfactants to achieve alkali excitation, thereby improving the performance and strength of the cementitious material. The cementitious material prepared by using the phosphogypsum-based polymer cementitious material raw material of the present invention has good cement-like properties, high strength, good water resistance and durability, and its various performance indicators are persistent and stable, and can be used to solve the problems of poor water resistance, low strength and poor durability of existing phosphogypsum cementitious materials. In addition, since the phosphogypsum-based polymer cementitious material raw material in the technical solution of the present invention does not contain cement, the risk of cement strength reduction or even specimen damage caused by the hydration reaction of traditional cement to generate calcium sulfonate is reduced.

[0045] Compared with common geopolymer products, the present invention effectively solves the problem of recycling solid waste materials by treating waste with waste and selecting phosphogypsum, steel slag, red mud and silicon slag as raw materials, avoids environmental pollution and occupation of arable land by phosphogypsum, and can achieve "treating waste with waste".

[0046] In an embodiment of the present invention, the raw material of the phosphogypsum-based polymer cementitious material further includes a retarder, and the retarder includes citric acid. The retarder can delay the setting and hardening speed of the cementitious material, reduce the hydration speed and hydration heat, and facilitate construction operations.

[0047] In an embodiment of the present invention, the raw materials of the phosphogypsum-based polymer cementitious material include the following components in parts by mass: 560 to 650 parts of phosphogypsum powder, 370 to 435 parts of active admixtures, 3.9 to 4.5 parts of water glass, 3.9 to 4.5 parts of sodium sulfate, 5.2 to 6.1 parts of silicon slag and 0.8 to 1.2 parts of calcium lignin sulfonate.

[0048] In an embodiment of the present invention, the raw materials of the phosphogypsum-based polymer cementitious material include the following components in parts by mass: 560 to 650 parts of phosphogypsum powder, 93 to 108 parts of steel slag powder, 280 to 325 parts of red mud powder, 3.9 to 4.5 parts of water glass, 3.9 to 4.5 parts of sodium sulfate, 5.2 to 6.1 parts of silicon slag and 0.8 to 1.2 parts of calcium lignin sulfonate.

[0049] It should be noted that too little water glass will lead to weak alkalinity, which is not conducive to the alkali-induced reaction. Too much water glass will lead to too strong alkalinity in the system solution, hindering the hydration reaction. The alkali-induced effect is smaller than the effect of the hindrance. Too much sodium sulfate will cause a large amount of SO4 in the solution. 2- In the early stage, a large amount of calcium aluminate is generated and wraps the slurry, which makes it impossible for water molecules to enter the slurry in the later stage, hindering hydration, thereby slowing down the strength growth. Too low sodium sulfate content has no obvious promoting effect on the alkali-induced reaction. When the silica slag content is too large, the slurry generates a large amount of CSH (hydrated calcium silicate) and AFt (monosulfur hydrated calcium aluminate sulfoaluminate) in the early stage, which will form a dense colloid on the surface of the unreacted slurry, making it impossible for the unhydrated silicate to hydrate, affecting the later strength growth of the specimen. Too little silica slag content is not conducive to the increase of the flexural strength of the specimen. Increasing the addition amount of calcium lignin sulfonate will make the mechanical properties of the cementitious material show a trend of first increasing and then decreasing. When the amount of calcium lignin sulfonate is set to 0.8-1.2 parts, the mechanical properties of the cementitious material are better.

[0050] In an embodiment of the present invention, the particle size of the phosphogypsum powder is less than 200 meshes. The phosphogypsum powder is obtained by drying and ball milling the original phosphogypsum, and the specific steps are as follows:

[0051] Take the original phosphogypsum, first use a drying oven to dry the phosphogypsum in a dry environment of 140°C for 4 hours, then grind it with a vertical planetary ball mill, and pass it through a 200-mesh square hole sieve for use.

[0052] Ball milling can effectively change the particle size distribution of phosphogypsum, making it more uniform, thereby improving the performance of the prepared cementitious material. The particle size of phosphogypsum will affect its hydration reaction and setting time. A smaller particle size helps to improve the fluidity and early strength of the material, but too small a particle size may increase the porosity, thereby reducing the overall strength of the material. The technical solution of the present invention sets the particle size of the phosphogypsum powder to be less than 200 meshes, ensuring that it is easy to process and obtaining a phosphogypsum-based cementitious material with good comprehensive performance.

[0053] In the embodiment of the present invention, the specific surface area of ​​the steel slag powder is 490m 2 / kg~510m 2 / kg. The steel slag powder is obtained by oven drying and ball milling of steel slag. A higher specific surface area can increase the contact area between steel slag and other raw materials, so that the cementitious material can reach the predetermined strength faster; a higher specific surface area can also help to form a denser and evenly distributed small pore network, thereby improving the compressive strength and durability of the material. However, as the specific surface area of ​​the admixture increases, the fluidity and workability will deteriorate. The technical solution of this application sets the specific surface area of ​​the steel slag powder to 490m 2 / kg~510m 2 / kg, has good processability, and the obtained phosphogypsum-based polymer cementitious material has good compressive strength and durability.

[0054] In an embodiment of the present invention, the particle size of the red mud is 0.3 mm to 0.5 mm. The red mud is dried, ground, and sieved to obtain red mud powder with a particle size of 0.3 mm to 0.5 mm. The red mud powder with a particle size of 0.3 mm to 0.5 mm is selected to prepare the phosphogypsum-based polymer cementitious material, which has a low production cost and a good compressive strength of the prepared cementitious material.

[0055] In the embodiment of the present invention, the silicon slag is silicon slag produced by the process of preparing aluminum fluoride with fluorosilicic acid. The silicon slag produced by the process of preparing aluminum fluoride with fluorosilicic acid contains a large amount of active SiO2 and A12O3·3H2O, which can promote the hydration of geopolymer materials.

[0056] In an embodiment of the present invention, the modulus of the water glass is 1.0 to 1.5, and the solid content is 35% to 40%. Water glass with a low modulus usually has a higher alkalinity, which can accelerate the alkali-induced reaction rate with the raw materials, but a lower modulus may also lead to too fast early strength development. Water glass within an appropriate modulus range helps to form a denser gel structure, thereby improving the strength and hardness of the material. Setting the modulus of the water glass to 1.0 to 1.5 has a better alkali-induced effect, which helps to obtain a phosphogypsum-based polymer gelling material with good comprehensive performance. Solid content refers to the proportion of non-water components (i.e., solid substances such as SiO2 and Na2O) in water glass. Using water glass with a solid content of 35% to 40%, water glass has good dispersibility in the raw material system and a suitable reaction rate, which is conducive to improving the overall strength and durability of the material.

[0057] In the embodiment of the present invention, the molecular weight of the calcium lignin sulfonate is 800 to 10000, the water content is less than or equal to 8%, and the lignin content is 50 to 65%. The calcium lignin sulfonate selected within the above range has a better effect of promoting the dispersion of the gelling material particles in the slurry and helps to fully carry out hydration.

[0058] The invention provides a method for preparing a phosphogypsum-based polymer gelling material, and adopts the raw materials of the phosphogypsum-based polymer gelling material to prepare the phosphogypsum-based polymer gelling material.

[0059] See also Figure 1 In one embodiment of the present invention, the method for preparing the phosphogypsum-based polymer cementitious material comprises the following steps:

[0060] The phosphogypsum powder, active admixture and alkali activator are mixed to obtain the phosphogypsum-based polymer gelling material.

[0061] The preparation method of the present invention mixes phosphogypsum powder, active admixture and alkali activator to prepare phosphogypsum-based polymer cementitious material. Compared with previous geopolymer products, it is a hydraulic cementitious material, which not only has good cement-like properties, but also has high strength, good water resistance and durability, and its various performance indicators are long-lasting and stable. The preparation method of the present invention has a simple preparation process, low cost, and is easy to implement. The materials used are low-carbon and energy-saving, safe and environmentally friendly, pollution-free, and can be used for a long time. It has low requirements on the construction environment, which is conducive to actual engineering applications, especially in road engineering, where a road roller can be directly used for flow operation to achieve large-scale production.

[0062] In an embodiment of the present invention, the step of mixing phosphogypsum powder, active admixture and alkali activator to obtain phosphogypsum-based polymer gelling material comprises:

[0063] The step of mixing phosphogypsum powder, active admixture and alkali activator to obtain phosphogypsum-based polymer gelling material comprises:

[0064] Mixing phosphogypsum powder, active admixture and water in a stirrer and stirring at a first rotation speed to obtain a first mixture;

[0065] Mixing the first mixture with a retarder in a stirrer and stirring at a second rotation speed to obtain a second mixture;

[0066] The second mixture is mixed with an alkali activator in a stirrer and stirred at a third speed to obtain a phosphogypsum-based polymer gelling material.

[0067] In an embodiment of the present invention, the first rotation speed is 500 r / min to 800 r / min.

[0068] In an embodiment of the present invention, the stirring time at the first rotating speed is 30 min to 50 min.

[0069] In an embodiment of the present invention, the second rotation speed is 150 r / min to 250 r / min.

[0070] In an embodiment of the present invention, the stirring time at the second rotating speed is 45 min to 60 min.

[0071] In an embodiment of the present invention, the third rotation speed is 150 r / min to 250 r / min.

[0072] In an embodiment of the present invention, the stirring time at the third rotating speed is 50 min to 60 min.

[0073] When preparing the phosphogypsum-based polymer gelling material, firstly, the phosphogypsum and the active admixture are fully stirred and mixed at high speed, then the corrosion inhibitor is added and stirred at low speed, and finally the alkali activator is added and stirred at low speed, so that the phosphogypsum and the active admixture are hydrated and reacted in an alkaline environment to generate the phosphogypsum-based polymer gelling material. Setting the first speed, the second speed, the third speed and the corresponding stirring time within the above range is conducive to uniform mixing of the raw materials.

[0074] It should be noted that the technical solution of the present invention has no limitation on the order of adding the alkaline activator, and the alkali activator can be added in the order of adding water glass, sodium sulfate, silicon slag and calcium lignin sulfonate, or the order of adding the materials can be adjusted.

[0075] The present invention provides a phosphogypsum-based polymer gelling material, wherein the phosphogypsum-based polymer gelling material is prepared according to the preparation method of the phosphogypsum-based polymer gelling material.

[0076] The invention provides an application of the phosphogypsum-based polymer cementitious material in preparing concrete.

[0077] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0078] In the following examples, the phosphogypsum is derived from a phosphogypsum storage yard in Xiangyang, Hubei Province, and is in the form of gray powder; the phosphogypsum powder is obtained by drying the phosphogypsum in a drying environment at 140° C. for 4 hours, then grinding it with a vertical planetary ball mill, and passing it through a 200-mesh square hole sieve;

[0079] The steel slag is derived from aged hot-stifled converter steel slag produced by Tangshan Donghai Iron and Steel Co., Ltd. The steel slag powder is obtained by drying the steel slag in a 105°C dry environment for 4 hours and then grinding it in a vertical planetary ball mill. The specific surface area of ​​the steel slag powder is 490m 2 / kg~510m 2 / kg;

[0080] The red mud comes from the red mud dump in Gaoshan Town, Xingyang, Henan Branch of Aluminum Corporation of China. The liquid limit of the red mud is 99.5%, the plastic limit is 47.2%, and the pH value is 10.86. The red mud powder is obtained by drying the red mud in a dry environment at 140° C. for 4 hours, grinding it with a vertical planetary ball mill, and sieving it. The particle size of the red mud powder is 0.3 mm to 0.5 mm.

[0081] The silicon slag is sourced from Henan Yebang Import and Export Co., Ltd.;

[0082] The water glass was purchased from Xi'an Mineral Chemical Research Institute Co., Ltd.

[0083] The calcium lignin sulfonate was purchased from Shandong Haoyao New Materials Co., Ltd.

[0084] Example 1

[0085] A method for preparing a phosphogypsum-based polymer gelling material:

[0086] Add phosphogypsum powder, steel slag powder, red mud powder and water into a stirrer, and stir at a speed of 500 r / min for 30 min to obtain a first mixture;

[0087] Adding citric acid to the first mixture, stirring at a speed of 150 r / min for 45 min, to obtain a second mixture;

[0088] Adding water glass, sodium sulfate, silicon slag and calcium lignin sulfonate to the second mixture in sequence, and continuing stirring at a speed of 150 r / min for 50 min to obtain a phosphogypsum-based polymer gelling material;

[0089] Wherein, the raw materials of the phosphogypsum-based polymer gelling material are:

[0090] 560 parts of phosphogypsum powder, 95 parts of steel slag powder, 280 parts of red mud powder, 380 parts of water, 4.0 parts of water glass, 4.0 parts of sodium sulfate, 5.2 parts of silicon slag, 0.8 parts of calcium lignin sulfonate and 8.4 parts of citric acid.

[0091] Example 2

[0092] A method for preparing a phosphogypsum-based polymer gelling material:

[0093] Adding phosphogypsum powder, steel slag powder, red mud powder and water into a stirrer, and stirring at a speed of 600 r / min for 40 min to obtain a first mixture;

[0094] Adding citric acid to the first mixture, stirring at a speed of 200 r / min for 50 min, to obtain a second mixture;

[0095] Adding water glass, sodium sulfate, silicon slag and calcium lignin sulfonate to the second mixture in sequence, and continuing stirring at a speed of 200 r / min for 55 minutes to obtain a phosphogypsum-based polymer gelling material;

[0096] Wherein, the raw materials of the phosphogypsum-based polymer gelling material are:

[0097] 600 parts of phosphogypsum powder, 100 parts of steel slag powder, 300 parts of red mud powder, 400 parts of water, 4.2 parts of water glass, 4.2 parts of sodium sulfate, 5.5 parts of silica slag, 1.0 part of calcium lignin sulfonate and 9.0 parts of citric acid.

[0098] Example 3

[0099] A method for preparing a phosphogypsum-based polymer gelling material:

[0100] Adding phosphogypsum powder, steel slag powder, red mud powder and water into a stirrer, and stirring at a speed of 800 r / min for 50 min to obtain a first mixture;

[0101] Adding citric acid to the first mixture, stirring at a speed of 250 r / min for 60 min, to obtain a second mixture;

[0102] Adding water glass, sodium sulfate, silicon slag and calcium lignin sulfonate to the second mixture in sequence, and continuing stirring at a speed of 250 r / min for 60 min to obtain a phosphogypsum-based polymer gelling material;

[0103] Wherein, the raw materials of the phosphogypsum-based polymer gelling material are:

[0104] 650 parts of phosphogypsum powder, 108 parts of steel slag powder, 320 parts of red mud powder, 430 parts of water, 4.5 parts of water glass, 4.5 parts of sodium sulfate, 6.0 parts of silica slag, 1.2 parts of calcium lignin sulfonate and 9.5 parts of citric acid.

[0105] Comparative Example 1

[0106] Compared with Example 2, the difference is that the dosage of sodium sulfate, silicon slag and calcium lignin sulfonate is 0.

[0107] Comparative Example 2

[0108] Compared with Example 2, the difference is that the dosage of sodium sulfate, silicon slag and calcium lignin sulfonate is 0, and sodium hydroxide is used instead of water glass.

[0109] Comparative Example 3

[0110] Compared with Example 2, the difference is that the dosage of sodium sulfate is 0.

[0111] Comparative Example 4

[0112] Compared with Example 2, the difference is that the amount of silicon slag used is 0.

[0113] Comparative Example 5

[0114] Compared with Example 2, the difference is that the amount of calcium lignin sulfonate used is 0.

[0115] Comparative Example 6

[0116] Compared with Example 2, the difference is that slag powder replaces steel slag powder, and fly ash replaces red mud powder; the grade of the slag powder is S95 (according to "Granulated blast furnace slag powder used in cement" (GB / T 18046)), which is off-white powder with a particle size of 1 to 60 μm; the grade of the fly ash is Class I (according to "Fly ash used in cement and concrete" (GB / T1596)), which is gray ultrafine powder.

[0117] Performance Testing

[0118] The phosphogypsum-based polymer cementitious materials prepared in Examples 1-3 and Comparative Examples 1-6 were prepared into test blocks and tested according to the test method of "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T17671-2020). The results are shown in Table 1 below.

[0119] Table 1 Performance test results of phosphogypsum-based polymer cementitious materials of Examples 1-3 and Comparative Examples 1-6

[0120]

[0121] It can be seen from Table 1 that the initial setting time of the phosphogypsum-based polymer cementitious materials of Examples 1-3 is not less than 45 minutes, which meets the construction requirements; the final setting time also meets the final setting time of silicate cement specified in "General Portland Cement" (GB 175-2007) (final setting time ≤ 390 minutes); the mechanical strength also meets the technical requirements of "General Portland Cement" (GB 175-2007) for cement materials (3d compressive strength ≥ 17MPa, 28d compressive strength ≥ 42.5MPa). It can also be seen from Table 1 that the compressive strength test results of Examples 1-3 are better than those of Comparative Examples 1-5, indicating that the addition of the composite alkali activator is beneficial to improving the compressive strength of the prepared cementitious material and reducing the initial setting time and the final setting time, and the effect is better when glass, sodium sulfate, silicon slag and calcium lignin sulfonate are used as alkali activators at the same time; the compressive strength test results of Examples 1-3 are also better than those of Comparative Example 6, indicating that compared with fly ash and steel slag powder, the use of steel slag powder and red mud powder as active admixtures is beneficial to improving the compressive strength of the prepared cementitious material.

[0122] In summary, the present invention selects solid wastes such as phosphogypsum, steel slag, and red mud as the main raw materials, and the obtained phosphogypsum-based polymer cementitious material has good cement-like properties, high strength, good water resistance and durability, and its various performance indicators are long-lasting and stable. Compared with ordinary geopolymer products, the present invention promotes the hydration reaction of the cementitious material by treating waste with waste, and exerts the alkali excitation effect through the compounding of inorganic salts and surfactants, thereby improving the performance and strength of the cementitious material. At the same time, the performance indicators of the phosphogypsum-based polymer cementitious material are long-lasting and stable, the preparation process is simple, the cost is low, and it is easy to implement. The materials used are low-carbon and energy-saving, safe and environmentally friendly, pollution-free, and can be used for a long time, which is conducive to solving the "stacking problem" and environmental pollution problems of waste asphalt materials, and meets the requirements of green, low-carbon and recycling engineering construction.

[0123] The above description is only an exemplary embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A raw material for a phosphogypsum-based polymer gelling material, characterized in that: The raw materials of the phosphogypsum-based polymer gelling material include phosphogypsum powder, active admixture and alkali activator; Wherein, the active admixture comprises at least one of steel slag powder and red mud powder; The alkali activator includes water glass, sodium sulfate, silica slag and calcium lignin sulfonate.

2. The raw material of the phosphogypsum-based polymer gelling material according to claim 1, characterized in that: The raw materials of the phosphogypsum-based polymer gelling material further include a retarder, and the retarder includes citric acid.

3. The raw material of the phosphogypsum-based polymer gelling material according to claim 1, characterized in that: The raw materials of the phosphogypsum-based polymer cementitious material include the following components in parts by mass: 560-650 parts of phosphogypsum powder, 370-435 parts of active admixtures, 3.9-4.5 parts of water glass, 3.9-4.5 parts of sodium sulfate, 5.2-6.1 parts of silicon slag and 0.8-1.2 parts of calcium lignin sulfonate.

4. The raw material of the phosphogypsum-based polymer gelling material according to claim 3, characterized in that: The raw materials of the phosphogypsum-based polymer cementitious material include the following components in parts by mass: 560-650 parts of phosphogypsum powder, 93-108 parts of steel slag powder, 280-325 parts of red mud powder, 3.9-4.5 parts of water glass, 3.9-4.5 parts of sodium sulfate, 5.2-6.1 parts of silicon slag and 0.8-1.2 parts of calcium lignin sulfonate.

5. The raw material of the phosphogypsum-based polymer cementitious material according to claim 1, characterized in that: The particle size of the phosphogypsum powder is less than 200 mesh; and / or, The specific surface area of ​​the steel slag powder is 490m 2 / kg~510m 2 / kg; and / or, The particle size of the red mud powder is 0.3 mm to 0.5 mm; and / or, The silicon slag is silicon slag produced by a process for preparing aluminum fluoride with fluorosilicic acid; and / or, The water glass has a modulus of 1.0 to 1.5 and a solid content of 35% to 40%; and / or, The molecular weight of the calcium lignin sulfonate is 800-10000, the water content is less than or equal to 8%, and the lignin content is 50-65%.

6. A method for preparing a phosphogypsum-based polymer gelling material, characterized in that: The phosphogypsum-based polymer cementitious material is prepared by using the raw material of the phosphogypsum-based polymer cementitious material according to any one of claims 1 to 5, and the preparation method of the phosphogypsum-based polymer cementitious material comprises the following steps: The phosphogypsum powder, active admixture and alkali activator are mixed to obtain the phosphogypsum-based polymer gelling material.

7. The method for preparing the phosphogypsum-based polymer gelling material according to claim 6, characterized in that: The step of mixing phosphogypsum powder, active admixture and alkali activator to obtain phosphogypsum-based polymer gelling material comprises: Mixing phosphogypsum powder, active admixture and water in a stirrer and stirring at a first rotation speed to obtain a first mixture; Mixing the first mixture with a retarder in a stirrer and stirring at a second rotation speed to obtain a second mixture; The second mixture is mixed with an alkali activator in a stirrer and stirred at a third speed to obtain a phosphogypsum-based polymer gelling material.

8. The method for preparing the phosphogypsum-based polymer gelling material according to claim 7, characterized in that: The first rotation speed is 500 r / min to 800 r / min; and / or, The stirring time at the first speed is 30 min to 50 min; and / or, The second speed is 150 r / min to 250 r / min; and / or, The stirring time at the second speed is 45 minutes to 60 minutes; and / or, The third rotation speed is 150 r / min to 250 r / min; and / or, The stirring time at the third rotating speed is 50 min to 60 min.

9. A phosphogypsum-based polymer cementitious material, characterized in that: The phosphogypsum-based polymer cementitious material is prepared according to the method for preparing a phosphogypsum-based polymer cementitious material according to any one of claims 6 to 8.

10. Use of the phosphogypsum-based polymer cementitious material according to claim 9 in preparing concrete.

Citation Information

Cited By

  • Ecological nutrient soil with ultrahigh absorption amount based on geopolymer modified ardealite and preparation method of ecological nutrient soil

    CN121286300A